PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE NUMBERED HEADS TOGETHER (NHT) UNTUK MENINGKATKAN HASIL BELAJAR MATEMATIKA SISWA KELAS III SDN 150 PEKANBARU - Astuti, Yeni; Marhadi, Hendri (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract. This research is motivated by the low value of math. Preliminary data result of learning students of class III of SD Negeri 150 Pekanbaru is from the 38 students, only 21 peoples or 55,26% completed or reached the KKM and 17 peoples or 44,74% were not completed. Based on these problems, it is necessary given way to solve the problem include applying Cooperative Learning Type Numbered Heads Together (NHT) model, the strategy to make students study together in teamwork. Data collection instrument on this research are observation sheet activities of teacher and student, and learning outcomes. Subjects in this research were students of class III of SD Negeri 150 Pekanbaru. This research was conducted in two cycles, by doing the daily test of the end of each cycle. The result of this research shows that the Numbered Heads Together (NHT) can increase math studies, increase of the basic score with an average of 75,26 (55.26%). increased in the each daily tests first cycle with an average of 84,74(73,68%) and increased on daily tests cycle II with an average of 86,05 (87%).Keywords : Numbered Heads Together (NHT), Mathematics Learning Outcomes.